KEDUDUKAN HUKUM NIKAH SIRI MENURUT MADZHAB SYAFI’I DAN MALIKI - Sahri, Ahmad; Arif, Suyud (MIZAN: JOURNAL OF ISLAMIC LAW, 2013)
Marriage is something that has been prescribed by religion. But in reality, people still have little understanding of the nature of marriage itself, so there is a carry but only run the Shari'a without ignoring other applicable rules. As well as Nikah Siri, although the law is considered valid marriage, but the rule of positive law in Indonesia has not considered valid. Therefore, raised view of the reviewer jurisprudence, especially from the schools of Shafi'i and Maliki.